Падежный синкретизм в истории славянских парадигм - Л. БАЛАЖ, ГАБОР (SlavVaria, 2021)
Case syncretism in the history of Slavic paradigms. The article is devoted to the problem of case syncretism. Specific definitions of this concept and the classification of its types from different periods of linguistic research are given. Further on, the issues of case syncretism are discussed, with special attention paid to its manifestation and regularities in the Slavic languages. The most common cases of syncretism in modern literary languages are presented and compared to the situation of the Common Slavic period. The problems of certain historical aspects of the formal concurrency of case endings and their possible causes are touched upon. The article concludes with a brief review of the theoretical explanations of syncretism and stresses the applicability of natural morphology to solve the questions posed.